Ultralow Overpotential in Rechargeable Li–CO2 Batteries Enabled by Caesium Phosphomolybdate as an Effective Redox Catalyst - Mahsa Masoudi; Neubi F. Xavier Jr; James Wright; Thomas M Roseveare; Steven Hinder; Vlad Stolojan; Qiong Cai; Robert C. T. Slade; Daniel Commandeur; Siddharth Gadkari (Advanced Science)
Abstract Rechargeable lithium‐CO2 batteries are emerging as attractive energy storage devices due to their potential for high capacity and efficient CO2 reduction, making them promising candidates for post‐lithium‐ion batteries with high energy densities. However, their practical applications have been restricted by low reversibility, poor cycle life, and sluggish redox kinetics induced by the high potential required for decomposing the discharge product Li2CO3. Despite the various cathode catalysts explored, their application is often limited by availability, high cost, and complexity of synthesis. Herein, caesium phosphomolybdate (CPM) is synthesized through a facile and low‐cost method. The Li‒CO2 battery based on the CPM cathode demonstrates a high discharge capacity of 15 440 mAh g−1 at 50 mA g−1 with 97.3% coulombic efficiency. It further exhibits robust stability, operating effectively over 100 cycles at 50 mA g−1 with a capacity limitation of 500 mAh g−1. Remarkably, the CPM catalyst yields a low overpotential of 0.67 V, surpassing most catalysts reported in prior research. This study reports, for the first time, the application of a Keggin‐type polyoxometalate as a bifunctional redox catalyst, significantly improving the reversible cycling of rechargeable Li–CO2 batteries.